Predictors of Airway Intervention in Angiotensin-Converting Enzyme Inhibitor-Induced Angioedema - Kieu, Monica Chau Q; Bangiyev, John N; Thottam, Prasad John; Levy, Phillip D (Otolaryngology-head and neck surgery, 2015)
Identify factors associated with angiotensin-converting enzyme inhibitor-induced angioedema (AIIA), including (1) time of presentation, (2) clinical symptoms, and (3) anatomical regions in the head and neck, that may indicate need for airway intervention. Case series with chart review. Three university tertiary care hospitals. Medical records of adult patients presenting to the emergency department (ED) diagnosed with AIIA within a 3-year period were reviewed. Time at presentation, presenting symptoms, physical examination findings, treatment, length of hospitalization, and outcomes were examined. Univariate analysis was performed. 311 patients were diagnosed with AIIA and evaluated with flexible laryngoscopy by an otolaryngologist. Patients requiring airway intervention most often presented within 4 hours of onset. Dysphagia, dysphonia, drooling, respiratory distress, and globus sensation were associated with airway intervention (χ(2) range, 9.1-47.1). Patients with edema of the face, lower lip, and upper lip were at low risk for airway intervention (odds ratio = 0.4, 0.3, and 0.4, respectively; all P values <.05), while those with involvement of the tongue, soft palate, vallecula, aryepiglottic folds, and true vocal cords were associated with highest risk (odds ratio = 11.1, 12.3, 9.9, 8.5, and 33.5, respectively; all P values < .001). This is the largest patient series to date of AIIA patients evaluated with flexible laryngoscopy. Physicians should be aware of certain risk factors that will require a higher acuity level of care, including (1) presentation within 4 hours of symptom onset, (2) symptoms such as drooling and respiratory distress, (3) and involvement of the tongue, soft palate, and larynx.